Tinjauan Yuridis terhadap Kendala Implementasi Kebijakan Pemekaran Desa di Kabupaten Bima - Adi Al Faisal; Taufik Firmanto; Amar Ma'arij (CV Rewang Rencang, 2025)
The formation and expansion of villages in Bima Regency are part of decentralization efforts to improve public services and regional development. However, this policy faces several obstacles, such as unsynchronized regulations between central and local governments and weak institutional capacity. This study employs a normative juridical method through document analysis to examine legal aspects and implementation. The findings reveal that the village expansion process has not been optimal and does not fully adhere to the principles of good governance. Therefore, strengthening local regulations and cross-sectoral coordination is necessary to achieve effective, transparent, and accountable village expansion policies.